Biallelic mutations in DNAJC12 cause hyperphenylalaninemia, dystonia, and intellectual disability - Anikster, Yair; Shen, Nan (The American journal of human genetics, 2017)
Phenylketonuria (PKU, phenylalanine hydroxylase deficiency), an inborn error of metabolism, can be detected through newborn screening for hyperphenylalaninemia (HPA). Most individuals with HPA harbor mutations in the gene encoding phenylalanine hydroxylase (PAH), and a small proportion (2%) exhibit tetrahydrobiopterin (BH4) deficiency with additional neurotransmitter (dopamine and serotonin) deficiency. Here we report six individuals from four unrelated families with HPA who exhibited progressive neurodevelopmental delay, dystonia, and a unique profile of neurotransmitter deficiencies without mutations in PAH or BH4 metabolism disorder-related genes. In these six affected individuals, whole-exome sequencing (WES) identified biallelic mutations in DNAJC12, which encodes a heat shock co-chaperone family member that interacts with phenylalanine, tyrosine, and tryptophan hydroxylases catalyzing the BH4-activated conversion of phenylalanine into tyrosine, tyrosine into L-dopa (the precursor of dopamine), and tryptophan into 5-hydroxytryptophan (the precursor of serotonin), respectively. DNAJC12 was undetectable in fibroblasts from the individuals with null mutations. PAH enzyme activity was reduced in the presence of DNAJC12 mutations. Early treatment with BH4 and/or neurotransmitter precursors had dramatic beneficial effects and resulted in the prevention of neurodevelopmental delay in the one individual treated before symptom onset. Thus, DNAJC12 deficiency is a preventable and treatable cause of intellectual disability that should be considered in the early differential diagnosis when screening results are positive for HPA. Sequencing of DNAJC12 may resolve any uncertainty and should be considered in all children with unresolved HPA.
Available online 26 January 2017
Gesehen am 18.06.2018